2008
DOI: 10.1002/pros.20825
|View full text |Cite
|
Sign up to set email alerts
|

Family history of prostate and breast cancer and the risk of prostate cancer in the PSA era

Abstract: Background-A family history of prostate cancer (PCa) or breast cancer (BCa) has been associated with the risk of PCa, but the risks were inconsistent in terms of the affected family members, and data in the PSA era are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 45 publications
5
71
2
2
Order By: Relevance
“…the grandfathers) were alive. It is important to ascertain family history in SDR in addition to FDR because, although cancer risk estimation has been based mainly on family history among FDR [8,9], family history among SDR may be informative in cancer risk assessment, particularly for sex-specific cancers, such as breast and prostate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the grandfathers) were alive. It is important to ascertain family history in SDR in addition to FDR because, although cancer risk estimation has been based mainly on family history among FDR [8,9], family history among SDR may be informative in cancer risk assessment, particularly for sex-specific cancers, such as breast and prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1.44 million new cases of invasive, non-skin cancers are estimated to have occurred in 2008 [1]. Site-specific cancer risk factors are not completely established and vary widely; however, a positive family history is a known risk factor for most malignancies [2,3,4,5,6,7,8,9]. Hereditary cancer syndromes, usually characterized by significant family history, account for only a small percentage of all cancer cases [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that as testosterone activates PSA transcription, the levels of testosterone generated by hormone treatment might be sufficient to induce PSA promoter transcription in bladder, and therefore CRE expression, and might thus activate Pim1 expression. This theory is supported by evidence that PSA is expressed in some bladder carcinomas [52][53][54].…”
Section: Discussionmentioning
confidence: 80%
“…Not only a family history of prostate cancer but also breast/ ovarian cancer increase the risk for men in a given familial line. In such case the relative risk is 1.7 and in the case of incidence of PC together with breast or ovarian cancer, the risk is 5.8 but results from other studies differ [14][15][16] . Segregate studies have found a mostly autosomal dominant heredity in patients with sporadic and familial prostate cancer.…”
Section: -45mentioning
confidence: 84%